Fossil manganese nodules from Sicily [5] - Jenkyns, H (1967)
FROM the stratigraphically condensed limestones of the West Sicilian Jurassic, which overlie a white Trias-Lias reefoid facies, Wendt recorded fossil ferromanganese nodules 1. © 1967 Nature Publishing Group.